MORONIC ACID: A REVIEW - RANI, RITU; SINGH, AJEET PAL; SINGH, AMAR PAL (International Journal of Current Pharmaceutical Research, 2021)
Moronic acid is a pentacyclic triterpenoid made up of olean-18-ene with an oxo group at position 3 and a carboxy group at position 28. It's made from an oleanane hydride. A few investigations have demonstrated that Moronic acid a wide scope of pharmacological effects such as Antidiabetic activity, Anti-AIDS agents, Chemotherapeutic agents, Virus lytic, Anti-HIV, Cytotoxic activity, Anti-herpes, Antimicrobial activity, Ribosome-loaded mRNAs.